Tasks completed by nursing members of a teaching hospital Medical Emergency Team. (February 2016) - Topple, Michelle; Ryan, Brooke; Baldwin, Ian; McKay, Richard; Blythe, Damien; Rogan, John; Radford, Sam; Jones, Daryl
Summary: Objectives: To assess tasks completed by intensive care medical emergency team nurses. Research design: Prospective observational study. Setting: Australian teaching hospital. Main outcome measures: Nursing-related technical and non-technical tasks and level of self-reported confidence and competence. Results: Amongst 400 calls, triggers and nursing tasks were captured in 93.5% and 77.3% of cases, respectively. The median patient age was 73 years. The four most common triggers were hypotension (22.0%), tachycardia (21.1%), low SpO2 (17.4%), and altered conscious state (10.1%). Non-technical skills included investigation review (33.7%), history acquisition (18.4%), contribution to the management plan (40.5%) and explanation to bedside nurses (78.3%), doctors (13.6%), allied health (3.9%) or patient/relative (39.5%). Technical tasks included examining the circulation (32%), conscious state (29.4%), and chest (26.5%). Additional tasks included adjusting oxygen (23.9%), humidification (8.4%), non-invasive ventilation (6.5%), performing an ECG (22%), and administrating fluid as a bolus (17.5%) or maintenance (16, 5.2%), or medication as a statim dose (16.8%) or infusion (5.2%). Self-reported competence and confidence appeared to be high overall amongst our MET nurses. Conclusion: Our findings provide important information on the tasks completed by Medical Emergency Team nurses and will guide future training.